Business Accounting and Finance - Gowthorpe, Catherine, 1956- (Andover : South-Western Cengage Learning, 2011)
Now in its third edition, this popular introductory text is aimed at non-specialist students of accounting and finance taking their first module in the subject, within courses such as business studies and management. The new edition has been extensively revised to bring all the financial reporting aspects up-to-date.
Previous ed.: 2005.
Includes index.
Keywords: Managerial accounting; Business enterprises -- Finance; Business and Management